Energizing Organizational Learning Process: Role Model for Increasing MSME Performance in Indonesia - Asep Saeful Falah; Aneu Yulianeu; Hendi Sobari (LKP DCI, 2023)
Paper This aim For test Energizing organizational Learning process effect on improvement the performance of embroidery MSMEs in Indonesia in dynamic environment . _ Survey quantitative carried out in the MSME Embroidery sector Tasikmalaya . For reach objective study empirical this , analyzed of 280 samples . Studies This offers a conceptual model for energizing organizational learning process on the increase the performance of embroidery MSMEs in Indonesia in dynamic environment . _ Findings showing that the energizing organizational learning process has effect positive on performance organizations in the embroidery MSME industry . Writer argue that energizing organizational learning process moderates leadership transformational and performance organization . one of the research suggestions more carry on is implementing energizing organizational learning with style leadership besides transformational eladership and implemented in umkm who don't use technology in help work his . studies This discuss gap in literature and practice leadership transformational , check interaction between energizing organizational learning processes and efficacy Work MSME team .